Psikologi Perkembangan dan Pendidikan Sekolah Dasar - Anwar, Rosihan; Neviyarni, Neviyarni; Zen, Zulhendri (TSAQOFAH, 2025)
Child developmental psychology serves as a fundamental basis in education, particularly at the elementary school level, as the ages of 6–12 represent a critical period for character formation, social skills development, and cognitive growth. This article aims to explore the principles and laws of child development and their application within the context of primary education. A descriptive qualitative approach was used, employing a literature review method based on various relevant scholarly sources. The findings indicate that understanding the stages and characteristics of child development is essential for teachers and parents in designing learning strategies tailored to students’ needs. Principles such as developmental individuality, continuity, and the interaction between environmental and hereditary factors serve as the foundation for creating adaptive and supportive learning environments. Furthermore, the application of developmental psychology in active learning has been shown to enhance student engagement, strengthen learning motivation, and foster the holistic growth of children’s potential. The article concludes that integrating developmental psychology into educational practices not only supports academic success but also contributes to strong character development. It is recommended that educators and policymakers adopt child development principles as a central reference in curriculum design and instructional strategies at the elementary level.